2015
DOI: 10.3109/00016357.2015.1046914
|View full text |Cite
|
Sign up to set email alerts
|

Effect of novel restorative materials and retention slots on fracture resistance of endodontically-treated teeth

Abstract: The preparation of retention slots may increase the fracture resistance of endodontically-treated teeth, especially, when restored with short fibre-reinforced composite. The use of short fibre-reinforced composite with retentive slots could be an alternative technique to prevent cuspal fracture on endodontically-treated teeth with MOD cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 27 publications
3
36
2
5
Order By: Relevance
“…In addition to the above‐mentioned studies, Kemaloglu et al., Yasa et al., Vahid et al., and Fráter et al. also evaluated SFRC as bulk base for large mesial‐occlusal‐distal (MOD) cavities in ETT . They concluded that the restoration of severely weakened teeth with the use of SFRC combined with conventional composites might have advantages over conventional composites alone.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the above‐mentioned studies, Kemaloglu et al., Yasa et al., Vahid et al., and Fráter et al. also evaluated SFRC as bulk base for large mesial‐occlusal‐distal (MOD) cavities in ETT . They concluded that the restoration of severely weakened teeth with the use of SFRC combined with conventional composites might have advantages over conventional composites alone.…”
Section: Resultsmentioning
confidence: 99%
“…Yasa et al 21 2016Avaliar a resistência à fratura de dentes tratados endodonticamente e restaurados com diferentes resinas compostas e diferentes preparos cavitários, com e sem slot de retenção In vitro, com molares humanos extraídos.…”
Section: In Vitro Com Molares Humanos Extraídosunclassified
“…Studies have shown that restoration of the remaining tooth structure with adhesive techniques can successfully improve the FR of restored tooth. However, the choice of partial coverage restoration that would provide the highest FR for endodontically treated posterior teeth under occlusal load remains debatable .…”
Section: Introductionmentioning
confidence: 99%
“…As there is a lack of consensus regarding the choice of material that is most suitable for the restoration of conservatively ETT ; the aim of the present in vitro study was to investigate the FR of endodontically treated mandibular first molars with conservative endodontic access cavity using different restoration techniques, under a static occlusal load.…”
Section: Introductionmentioning
confidence: 99%